2016
DOI: 10.1002/mds.26677
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evidence in support of a knock‐in mouse model of DYT1 Dystonia

Abstract: Background DYT1 dystonia is an autosomal dominant movement disorder characterized by abnormal, often repetitive, movements, and postures. Its hallmark feature is sustained or intermittent contractions of muscles involving co-contractions of antagonist muscle pairs. The symptoms are relieved with the anticholinergic drug trihexyphenidyl. The primary mutation is a trinucleotide deletion (ΔGAG) in DYT1/TOR1A, which codes for torsinA. Previous studies showed that (1) heterozygous Dyt1 ΔGAG knock-in mice, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…An alternative viewpoint is that the observations could be compensatory for the underlying pathophysiology. A number of studies have shown that cortico-striatal synaptic efficacy (i.e., LTD) and impaired motor function are restored in Dyt1 KI (Dang et al, 2012; DeAndrade et al, 2016; Maltese et al, 2014) and KO (Liang et al, 2014; Pappas et al, 2015) mice following the administration of anticholinergic therapeutics. As such, future studies focused on elucidating restorative effects of anticholinergic medications on functional connectivity abnormalities will prove to be important in supporting the position that impaired basal ganglia connectivity manifests as a function of disease-specific pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative viewpoint is that the observations could be compensatory for the underlying pathophysiology. A number of studies have shown that cortico-striatal synaptic efficacy (i.e., LTD) and impaired motor function are restored in Dyt1 KI (Dang et al, 2012; DeAndrade et al, 2016; Maltese et al, 2014) and KO (Liang et al, 2014; Pappas et al, 2015) mice following the administration of anticholinergic therapeutics. As such, future studies focused on elucidating restorative effects of anticholinergic medications on functional connectivity abnormalities will prove to be important in supporting the position that impaired basal ganglia connectivity manifests as a function of disease-specific pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, previous work has reported that Dyt1 KI mice elicit impaired inhibitory modulation of cortical evoked potentials via striatal HFS in vitro (Dang et al, 2012). Moreover, abnormal sensorimotor evoked functional connectivity may account for recent evidence that the Dyt1 KI mouse model elicits sustained EMG activity and intermittent co-contractions of the biceps and rectus femori muscles (DeAndrade et al, 2016). These findings are in line with previous human studies that have reported increased volumetric grey-matter changes and amplified somatosensory activation in accounting for the overflow of conflicting cortical motor commands (i.e., SI) in patients with writer’s cramp, orofacial dystonia, and focal hand dystonia (Dresel et al, 2006; Garraux et al, 2004; Lerner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations